Soil properties of agricultural area in karst terrain of Parakan, Pangandaran, West Java, Indonesia - Reginawanti Hindersah; Yusi Firmansyah; Nia Kurniati (Journal of Degraded and Mining Lands Management, 2021)
a clayed soil characterized by reddish in colour, thick solum and neutral acidity. Farmers in Parakan area, Parigi District of Pangandaran, usually cultivate cash crops in terra rossa. Nowadays, farmers have no information about the properties of the soil, which is an important factor to maintain and increase plant productivity. The objective of this descriptive quantitative study was to verify the soil characteristic included physicochemical and microbiological properties in a selected agricultural field of Parakan. The soil samples were taken from three different areas covered with different vegetation. The study showed that terra rossa in the karst area is a non-saline soil with neutral acidity and low electrical conductivity. The texture of all soils were clay contained >50% clay particle. The soils were low in organic carbon, total nitrogen and available phosphor; but high in total phosphor and potassium, as well as cation exchange capacity. The population of soil microbes include total and fungal bacteria, as well as nitrogen-fixing Azotobacter and phosphate solubilizing bacteria, were average. In order to increase the organic carbon level; and the availability of phosphor and nitrogen, organic matter amendment is needed.